THERMAL ANALYSIS OF HEAT TRANSFER THROUGH FINS OF A FOUR STROKE INTERNAL COMBUSTION ENGINE USING DIFFERENT RESEARCH OCTANE NUMBER (RON) GASOLINE FUELS - IDRUS, FAIROSIDI; YAAKOB, YUSLI; MOHD NORHISHAM, MUHAMMAD WAFIQ FARHAT (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2024)
ABSTRACT - The heat transfer processes in an internal combustion engine can be modelled with a variety of methods. These methods range from simple thermal networks to multi-dimensional differential equation modelling. For thermal analysis of the engine cylinder fins, it is more beneficial to know the heat dissipation inside the cylinder. Fins are placed on the surface of the cylinder to enhance the amount of heat transfer by convection. The goal of this research is fo analyse and compare the heat dissipation through rectangular fins of a four-stroke internal combustion (IC) engine of using different Research Octane Number (RON) gasoline fuels; RON 95, RON 97, and RON 100. An experiment has been conducted on a single-cylinder four-stroke IC engine in a Thermodynamics laboratory and the temperature on the cylinder fins surface are measured by using an infrared thermometer. The fins are designed by SOLIDWORKS and the thermal analysis is carried out by ANSYS. The thermal analysis data indicates that there is @ corresponding rise in temperature for RON 100, indicate superior resistance to knocking in comparing to RON 95 and RON 97. RON 100 consistently exhibited the highest temperatures on the fins, implying potential variations in heat dissipation and combustion efficiency.